Rural marketing as a tool for mational development : strategies for socio-economic progress - Chatterjee, Charles (Emerald Publishing Limited, 2024)
Rural marketing entails applying marketing strategies customized for rural areas to enhance the economic and social welfare of the communities it serves. It aims to generate demand for affordable goods and services while fostering interest and skill-building among rural populations. Rural Marketing as a Tool for National Development: Strategies for Socio-Economic Progress delves into the multifaceted realm of rural marketing and its impact on national advancement. It covers fundamental concepts, the adaptation of strategies to different rural settings, and the promotion of interest and skill-building among rural communities. The study also scrutinizes the intricate nature of development, underscoring the significance of indigenous wisdom and participatory governance. By shedding light on obstacles such as urban biases and governmental oversight, it delves into regulatory frameworks, financial hurdles, and the socio-economic opportunities inherent in rural marketing. Additionally, the integration of environmental sustainability into rural development is explored, drawing insights from global initiatives. This work benefits a wide range of professionals and academics, including those in marketing, rural studies, policymaking, government studies, business, entrepreneurship, environmentalism and sustainability.
Keywords: Rural development.; Marketing.; Business & Economics -- Development -- General.; Rural planning and policy.; Development economics and emerging economies.; elektronické knihy; electronic books